Membangun Generasi Anti-Judol dan Pinjol: Program Pengabdian Masyarakat di SMK Humanika - Mufidah, Vika Nurul; Ulum, Aditya Nur Roisul; Setia, Dindi Gesit; Adha, Aniqoh Fawwaz Febriani; Akbar, Farah Nabila (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
This community service activity was conducted on Friday, 28 November 2025, at SMK Humanika, Ciherang, Bogor, with the aim of improving students’ digital and financial literacy as a preventive effort against adolescent involvement in online gambling and illegal online lending practices. The activity employed classroom-based education, case study–based material delivery, interactive simulations, and focused group discussions to encourage active student participation. The evaluation was carried out using pre-test and post-test assessments as well as observations of student engagement. The results indicate an improvement in students’ understanding of the legal, social, and psychological risks associated with online gambling and online lending, as reflected in increased post-test scores and students’ ability to identify and formulate school-based prevention strategies. The participatory and contextual approach proved effective in enhancing students’ critical awareness and decision-making skills. This community service initiative underscores the importance of integrating digital and financial literacy as well as anti–online gambling and online lending education into school programs as a sustainable effort to develop resilient youth who are protected from the risks of illegal digital practices.